A Study of Early Buddhist Views on Illness and Suffering: A Case of Eighteen Fragments in Chinese Version Saṁyukta Āgama - Jinying WANG (Yixue yu zhexue, 2025)
The Chinese version of Saṁyukta Āgama is one of the early Buddhism classics, containing numerous discussions on "illness and suffering" and the Buddhism perspective on it. By analyzing 18 case studies from the "illness-related discourses" section and referencing other early Buddhism texts, this paper explores the early Buddhist understanding of suffering caused by illness in four aspects just as the Catursatya contains: the truth of suffering (acknowledging the physical and mental pain brought by illness), the origin of suffering (recognizing impermanence and identifying the root causes), the cessation of suffering (actively seeking treatment and healing), and the path to the cessation of suffering (undertaking specific practices to achieve physical recovery or spiritual elevation). This view offers profound insight into achieving ultimate liberation—nirvāṇa—through engagement with the reality of illness. The early Buddhist perspective on illness and suffering holds significant contemporary value for addressing patients' pain and promoting physical-mental harmony.